Water and sanitation practices at household level in Rupa Rural Municipality, Kaski, Nepal - Banstola, Sanju; Koirala, Sharad; Bhandari, Ishwori (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Water, sanitation, and hygiene-related infrastructure, practices, and services are crucial preconditions for stopping the spread of illness. Thus the study aimed to assess the household-level sanitation and water practices in Rupa Rural Municipality, Kaski, Nepal.Methods: A cross-sectional study was conducted among household in Rupa Rural Municipality of Kaski district, Nepal. The study was conducted from October 6 to October 16, 2024. Observation checklist was used for observation of water and sanitation practices.  Waste segregation, waste management, water purification, toilet availability, whether the toilet was clean, and the presence of soap and water in the toilet were all taken into consideration while evaluating the dependent variable. These objects were divided into two categories, 0 and 1. Following the addition of these criteria, sanitation practices were grouped according to mean values. Chi-square tests was applied at 5% level of significance.Results: Out of 384 households, 75.80% reported having a separate kitchen in their home. Majority (81%) said they separated their garbage, and 55.8% had effective waste disposal practices. More than half (52.30%) of the water in the home was filtered. Among the total household, 80% had good sanitation practices while 20% had poor sanitation practices. The results show that there was a significant association of age and religion of household with the sanitation practices.  Conclusions: The study highlights there was gap in hygiene behavior and sanitation practices at household level. More attention must be paid to infrastructure investments that enable effective waste management services and water purification.